The predictive role of psychological status and disease severity indexes on quality of life among patients with non-CF bronchiectasis - KOCAKAYA, DERYA; OLGUN YILDIZELİ, ŞEHNAZ; ERYÜKSEL, SEMİHA EMEL; CEYHAN, BERRİN (My University, 2022)
OBJECTIVE: Bronchiectasis is a chronic suppurative lung disease that significantly impacts the patients\" quality of life. The aim of this study is to evaluate the relationship between quality of life and patient\"s psychological status and bronchiectasis disease severity indexes in patients with non-cystic fibrosis bronchiectasis. We also aimed to investigate the validity and reliability of Turkish version of Quality of Life Questionnaire-Bronchiectasis (V3.1) in Turkish adult bronchiectatic patients.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Medicine; Health Sciences; Internal Medicine Sciences; Chest Diseases and Allergy; SOLUNUM SİSTEMİ; Klinik Tıp; Klinik Tıp (MED); RESPIRATORY SYSTEM; CLINICAL MEDICINE; Clinical Medicine (MED); Respiratory Care; Pulmonary and Respiratory Medicine; Anxiety; depression; non-CF bronchiectasis; quality of life; QUESTIONNAIRE-BRONCHIECTASIS; PSYCHOMETRIC ANALYSES; DEPRESSION; ANXIETY; VALIDATION; VALIDITY